FUNGSI PENGAWASAN BADAN PERMUSYAWARATAN KEPENGHULUAN (BPKep) DI KEPENGHULUAN BANGKO PUSAKA KECAMATAN BANGKO PUSAKA KABUPATEN ROKAN HILIR TAHUN 2015 - Royazali "; Isril " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Village consultative bodies are institutions that have a function of oversight of the performance of the village head according to the mandate in law No. 6 of 2014 article 55. Supervision is done to prevent deviations made by the elements in the village administration. Performance monitoring of a village head is seen from the achievements of the policies he applied in the village. To measure the performance of the village head, BPD has the right to request the Village Head Accountability Report within one year. This research would like to see how the supervisory function of the Village Consultative Board in Kepenghuluan Bangko Pusaka Bangko Pusako Sub-district of Rokan Hilir Regency. The purpose of this study is to determine the implementation of supervision on the performance of village heads in Kepenghuluan Bangko Pusaka by Kepenghuluan Kepenghuluan Agency Year 2015. The location of this study was conducted in Kepenghuluan Bangko Pusaka District Bangko Pusako Rokan Hilir Regency. The method used in this research is descriptive method with qualitative approach. Data collection techniques in this study are interviews and documentation. Data analysis technique used is descriptive qualitative data analysis. The result of this research is Supervision of Deliberation Board of Kepenghuluan Bangko Pusaka not optimal in performing its duty. Some of the village chief's policy programs did not go according to plan and did not work. based on interview results there are several facts in the field; 1. the LPJ village head's discussion by BPD is not Qorum, 2. Accountability Report no response from members of BPD. Keywords: supervision, performance of village head. village government.